Islam and Psychology: Research Approaches and Theoretical and Practical Implications (American Journal of Islam and Society, 2022)
Religion and spirituality have increasingly gained attention as resilience factors in mental health, and as common factors in psychotherapy.1 To this end, Muslim academics and clinicians across the globe have also begun to develop Islamically-integrated therapeutic interventions and services.2 Nevertheless, this area attracts controversies among Muslim experts from different disciplines such as psychology, psychotherapy, psychiatry, and Islamic theology. For instance, there is still no consensus concerning the definition and kinds of theoretical and practical permutations between the canon of Islamic disciplines and modern psychology.To address this fundamental question at the level of a conference for the first time in continental Europe, the Islamic Association of Social and Educational Professions (IASE) brought together a group of approximately 65 Muslim students, counselors, therapists, psychiatrists, and Islamic theologians from across Germany, Austria, and Switzerland in Frankfurt am Main on April 6, 2019.